Design and development of compressed air engine - Mahato, Aplesh Kumar; Sharma, Dinanath; Bastakoti, Durga; Shrestha, Min Narayan; Bhatt, Niraj; Koirala, Rajeshwor (Journal of Engineering Issues and Solutions, 2023)
This research aims to build an engine that uses compressed air as a fuel to provide mechanical energy to rotate a crankshaft which can be used for useful work. The specific objectives of the study are to design and fabricate a compressed air engine within a pressure range of two to five bar and to test the engine's performance in terms of angular velocity of the crankshaft, torque produced at the crankshaft, stress and displacement analysis on the base frame and efficiency of the engine. To achieve these objectives, design equations of inertial forces in reciprocating parts is used to calculate the torque produced at the crankshaft, computational tool is used to calculate the stress and displacement analysis on the base of the frame and experimentally the engine is tested to calculate the angular velocity at the crankshaft and valve timing so that crankshaft produces uniform rotational motion. It was found that, the angular velocity is directly and Arduino valve timing is inversely proportional to the pressure exerted by the piston. A force of 245.43 N is exerted by the pneumatic piston cylinder when rotated at 100 RPM producing a torque of 45 Nm at efficiency of 29.60%. The base frame exerted a maximum stress of 48 Mpa and maximum displacement of 1.9 mm, both at the location at which the crankshaft is installed. It is important to note that the results may not be generalizable to all compressed air engines and further research is needed to fully understand their performance and capabilities.